The warlord - Showalter, Gena (Showalter, Gena. Rise of the warlords, 2021)
For a chance to save her people, Taliyah Skyhawk must wed the fearless leader of the Astra Planeta, Alaroc Phaethon, but the ice maiden and the merciless king never anticipated their battles turning into games that only one spouse can win.